Deciphering the reaction mechanisms of photothermal hydrogen production using H/D kinetic isotope effect. Issue 17 (10th August 2022) - El Hakim, Sara; Chave, Tony; Nikitenko, Sergey I.
Abstract : Large H/D isotope separation coefficient and its variation with temperature indicates a hole-mediated O–H bond cleavage as the limiting stage of photothermal hydrogen production. Abstract : H/D kinetic isotope effect has been employed to study the mechanism of the thermally assisted photocatalytic hydrogen production over noble metal-free Ti@TiO2 core–shell nanoparticles. We have found that the observed large H/D isotope separation factor ( α H = 11.3 ± 1.7–6.2 ± 0.9) is due to the electron hole-mediated cleavage of OH bond. It was concluded that strong H/D isotopic selectivity is associated with significant photothermal effect.